1990
DOI: 10.1016/s0006-3495(90)82495-4
|View full text |Cite
|
Sign up to set email alerts
|

General analysis of receptor-mediated viral attachment to cell surfaces

Abstract: Viruses are multivalent particles that attach to cells through one or more bonds between viral attachment proteins (VAP) and specific cellular receptors. Three modes of virus binding are presented that can explain the diversity in binding data observed among viruses. They are based on multivalency of attachment and spatial versus receptor saturation effects which are easily distinguished based upon simple criteria. Mode 1 involves only monovalent virus/receptor binding. Modes 2 and 3 involve multivalent bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 51 publications
6
69
0
2
Order By: Relevance
“…This is most likely due to the significantly lower affinity of the Ad7 and Ad14 knobs for CD46, which would require micromolar concentrations of fiber knobs to achieve a measurable blockage of Ad11 binding. Total blockage of Ad11 binding was never observed, probably due to nonspecific binding or binding to secondary or additional receptors (50,53). Ad-blocking experiments usually do not result in complete blocking, as was also observed by others (43,44).…”
Section: Vol 83 2009 a Species B Ad Knob Switch Determines Engagemementioning
confidence: 57%
“…This is most likely due to the significantly lower affinity of the Ad7 and Ad14 knobs for CD46, which would require micromolar concentrations of fiber knobs to achieve a measurable blockage of Ad11 binding. Total blockage of Ad11 binding was never observed, probably due to nonspecific binding or binding to secondary or additional receptors (50,53). Ad-blocking experiments usually do not result in complete blocking, as was also observed by others (43,44).…”
Section: Vol 83 2009 a Species B Ad Knob Switch Determines Engagemementioning
confidence: 57%
“…(total liposome projected area)/(cell surface area)], where k f,0 is the association rate in the absence of any steric limitations (36). It is also assumed that liposomes cannot freely access the portion of the cell surface that is adherent to the tissue culture plastic-roughly 50%.…”
Section: Kinetic Computational Modelmentioning
confidence: 99%
“…Therefore, we investi- gated the mode and kinetics of baculovirus entry into mammalian cells. Baculovirus is taken up in insect cells by receptormediated endocytosis, followed by pH-dependent fusion of the envelope with the endosome (3,34). It has been suggested that baculovirus enters mammalian cells by the same pathway because chloroquine strongly inhibits marker gene expression (6,17).…”
Section: Infection Of Mammalian Cells By Baculovirusmentioning
confidence: 99%
“…It has a 130-kb double-stranded DNA genome, packaged in a cigar-shaped (25 by 260 nm) enveloped nucleocapsid. Baculovirus enters insect cells via receptor-mediated endocytosis (32,34). The viral fusion protein gp64 is responsible for acid-induced endosomal escape (3).…”
mentioning
confidence: 99%